Flashback - Barr, Nevada (New York : G.P. Putnam's Sons, 2003)
Taking a temporary post as ranger in Dry Tortugas National Park to escape dealing with a marriage proposal, Anna Pigeon investigates a mysterious boating accident that leads her to uncover sinister local crimes from the past.
Map on lining pages.
Keywords: Pigeon, Anna (Fictitious character) -- Fiction; Women park rangers -- Fiction; Dry Tortugas National Park (Fla.) -- Fiction; Florida -- Fiction; Mystery fiction